PENGEMBANGAN FILM TRANSDERMAL DILTIAZEM HCl TIPE MATRIKS DENGAN KOMBINASI POLIMER POLIVINIL ALKOHOL DAN ETIL SELULOSA SERTA PENINGKAT PENETRASI PEG 400 - Yulias Ninik Windriyati; Aenul Sholikhah; Fauziah Muliawati (Jurnal Ilmu Farmasi dan Farmasi Klinik, 2016)
ABSTRACT Diltiazem hydrochloride (diltiazem HCl), a calcium channel blocker is widely used in the management of angina pectoris and hypertension. Because of its short biological half-life (3.5 h) and low oral bioavailability (40%) due to extensive hepatic metabolism leading to high frequency drug dosing. Therefore, diltiazem HCl is a suitable drug for transdermal formulation to improve bioavailability of the drug, patient’s convenience and compliance due to less frequent administration. The objective was to characterized the physicochemical properties and permeation of matrix film transdermal diltiazem HCl that prepared with polymers (PVA & EC) and PEG 400 as penetration enhancer. In this study, six formulation were prepared in different ratio of film forming polymers (5:5 & 7:3),  and 15%, 20%, 25% of PEG 400. Developed transdermal film  were characterized for  weight uniformity, thickness, folding endurance, moisture uptake, drug content and in vitro permeation study using commercial semi permeable membrane. The crystall of drug excipient interaction  were evaluated using X-ray diffraction technique. All the formulations were found to be suitable for formulating in terms of physicochemical characteristics and there was no significant differences. The in vitro skin permeation profiles showed increased flux values with increase  of PEG 400  as penetration enhancer. The X-ray diffraction studies revealed that the crystallinity of the drug decreased as the proporsion of PVA in the film increased.  Keywords : diltiazem HCl, PEG 400, PVA, patch transdermal, permeation